Synthesis of Cr2O3 Nanoparticle-Coated SnO2 Nanofibers and C2H2 Sensing Properties - Gao, Xin; Zhou, Qu; Lu, Zhaorui; Xu, Lingna; Zhang, Qingyan; Zeng, Wen (Frontiers in Materials, 2019)
In this work, Cr2O3 nanoparticles and SnO2 nanofibers were fabricated by a sol–gel process and an electrospinning method, respectively. Gas sensitive materials with high sensitivity to C2H2 gas were obtained by coating Cr2O3 nanoparticles on SnO2 nanofibers. The prepared Cr2O3 nanoparticle-coated SnO2 nanofibers (Cr2O3 NPs. coated SnO2 NFs.) were characterized by X-ray diffraction (XRD), scanning electron microscope (SEM), X-ray energy dispersive spectroscopy (EDS), X-ray photoelectron spectroscopy (XPS) and the gas sensing behaviors to C2H2 were studied. The Cr2O3 NPs. coated SnO2 NFs. exhibited low optimal operating temperature, high sensing response, excellent response-recovery time and long-term stability to C2H2. The optimal operating temperature of the measured material to 20 ppm C2H2 was about 220℃ and the C2H2 concentration had a good linear relationship with the response value when the concentration was less than 60 ppm. In addition, a reasonable gas sensing mechanism was proposed which may enhance the gas sensing performances for the Cr2O3 NPs. coated SnO2 NFs. to C2H2.